A comparative study of the normal oesophageal wall thickness based on 3-dimensional, 4-dimensional, and cone beam computed tomography. Issue 45 (6th November 2020) - Hu, Chao Yue; Li, Yan Kang; Li, Jian Bin; Wang, Jin Zhi; Shao, Qian; Wang, Wei; Guo, Yan Luan; Xu, Min; Li, Wen Wu
Abstract: Background: The study aimed to compare normal oesophageal wall thickness based on 3-dimensional computed tomography (3DCT), 4-dimensional computed tomography (4DCT) and cone beam computed tomography (CBCT). Methods: Contrast-enhanced 3DCT, 4DCT, and CBCT scans were acquired from 50 patients with lung cancer or metastatic lung cancer. The outer oesophageal wall was manually contoured on each 3DCT, the maximum intensity projection of 4DCT (4DCTMIP ) the end expiration phase of 4DCT (4DCT50 ) (the end expiration phase of 4DCT) and the CBCT data sets. The average wall thicknesses were measured (defined as R3DCT, R50, RMIP, and RCBCT ). Results: Whether for thoracic or for intra-abdominal segments, there were no significant differences between R3DCT and R50, but significant differences between R3DCT and RMIP, R3DCT and RCBCT . For upper and middle oesophagus, RCBCT were larger than RMIP . There was no significant difference between upper and middle segments on 3DCT, 4DCT, and CBCT. Intra-abdominal oesophageal wall thickness was greater than that of thoracic oesophagus. There were no differences between upper and lower, and middle and lower oesophagus on CBCT. Conclusion: Our findings indicate normal oesophageal wall thickness differed along the length of oesophagus whatever it was delineated on 3DCT, 4DCT (4DCT50 and 4DCTMIP ) or CBCT. It is reasonable to use uniform criterion to identify normal esophageal wall thickness when delineating gross tumor volume on 3DCT and 4DCT50, the same is true of delineating internal gross tumor volume on 4DCTMIP or CBCT images for lower and intra-abdominal oesophagus. But, in spite of using contrast-enhanced scanning, relatively blurred boundary on the CBCT images is noteworthy, especially for upper and middle thoracic esophagus.